’My Mind Starts Craving’ - Impact of Resealable Packages on the Consumption Behavior of Indian Consumers - Nayyar, Varun (Indian Journal of Marketing, 2018)
Packaging of products has started nudging the consumers with its dynamic attributes, where resealable has become one of the distinctive attributes which has modified the consumption behavior of Indian consumers. A store shelf of every retail outlet has the presence of different types of packaging of products, but the major advantage of the resealable attribute is that it can repack the product in order to prolong the shelf life of that particular item warehoused inside the resealable packaging. Here, the research intended to gauge whether this particular feature had any implication on the freshness and whether it reduced the consumption level of high calorie products warehoused in these types of packaging. This study tried to uncover the behavioral evidence of consumers related to their self-regulation in their consumption patterns for high calorie products when offered in resealable packaging in comparison to non-sealable packaging with the assistance of research techniques like chi-square & F-test. The results revealed that resealable attribute of packaging limited the compounded consumption pattern of consumers with respect to junk food (chips in the present study). This research also suggested remindful measures for corporate players to offer packaging which culminates in creating good nutrition and a healthy environment for the consumers.